2022
DOI: 10.1039/d1ee02518j
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted high-performance PtRu alloy for pH-universal hydrogen evolution

Abstract: Elucidating the interaction between different atomic species of the bimetallic nanoparticles under reaction conditions is key to the design of efficient catalysts. Here, we report a laser-assisted strategy towards PtRu...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…Therefore, researchers have focused on designing electroactive materials with low cost and highly abundant transition metals, which can maintain higher stability and higher efficiency for large scale hydrogen production. Currently, rst row transition metalbased catalysts such as nitrides, 10,11 carbides, 12 selenides, 2 and sulphides have a major role towards HER 13,14 and transition metal oxides, hydroxides, and oxyhydroxides are active towards OER. 7,15 In this regard, currently, layered double hydroxides (LDHs) have gained greater attention from researchers worldwide, owing to their earth-abundant, low cost, and highly stable nature in alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have focused on designing electroactive materials with low cost and highly abundant transition metals, which can maintain higher stability and higher efficiency for large scale hydrogen production. Currently, rst row transition metalbased catalysts such as nitrides, 10,11 carbides, 12 selenides, 2 and sulphides have a major role towards HER 13,14 and transition metal oxides, hydroxides, and oxyhydroxides are active towards OER. 7,15 In this regard, currently, layered double hydroxides (LDHs) have gained greater attention from researchers worldwide, owing to their earth-abundant, low cost, and highly stable nature in alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of hydrogen energy is considered to be one of the important ways to reduce CO 2 emissions from traditional fossil fuel combustion. The water splitting is an efficient and clean approach to develop hydrogen energy, especially using the electricity generated by renewable energy. The recognized catalyst used to produce hydrogen efficiently through water splitting is the expensive and scarce Pt, which shows the best hydrogen evolution reaction (HER) performance for the most appropriate metal–H bond strength according to the typical Sabatier principle . However, this principle alone cannot explain the phenomenon that the HER activity of Pt under alkaline media is 2–3 orders of magnitude worse than that under acidic media. ,, It is suggested that the energy barrier of water dissociation under alkaline media is the key factor restricting the catalyst’s HER activity. , The recent studies show that ruthenium (Ru), which costs only about one-third of the price of Pt, shows superb HER activity under acidic or alkaline media. , Thanks to the water dissociation and *OH chemisorption capacity, many Ru-based catalysts show better HER performance than Pt under alkaline media. ,, …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In practice, room-temperature water electrolysis can be carried out in both acidic and alkaline electrolytes, where platinum-based nanoparticles generally serve as the catalysts of choice. [7][8][9][10] However, the high cost, scarcity, and sluggish kinetics (about two orders of magnitude lower in alkaline electrolytes than that in acid) of platinum-based materials have greatly hampered the widespread application of electrochemical water splitting technology. 11 Thus, developing viable alternatives that are of low cost and high performance for the HER in alkaline electrolytes is of both fundamental and technological signicance.…”
Section: Introductionmentioning
confidence: 99%